Analisis Studi Kelayakan Bisnis Pada UMKM Di Tinjau Dari Aspek Pasar Dan Pemasaran (Studi Kasus UMKM Jinji Dimsum ) - Milawati Dewi; Nilam ayuningtyas; Dwi astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research analyzes the business feasibility of Jinji Dimsum MSMEs from market and marketing aspects. Dimsum, a popular food originating from China, has attracted the attention of Indonesians, especially young people. The research method used is qualitative with literature study and marketing strategy analysis. The results show that Jinji Dimsum successfully positioned itself as a provider of quality dimsum at affordable prices, and implemented effective marketing strategies through social media and collaboration with influencers. The 4P marketing mix (product, price, promotion, and place) applied increases brand awareness and expands market reach. In conclusion, Jinji Dimsum MSMEs are able to build strong competitiveness and create sustainable growth opportunities in the culinary industry.